2023
DOI: 10.1111/phpp.12914
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ultraviolet radiation on cardiovascular and metabolic disorders: The role of nitric oxide and vitamin D

Qing‐Ling Quan,
Kyeong‐No Yoon,
Ji Su Lee
et al.

Abstract: Background/PurposeUltraviolet (UV) radiation has both harmful and beneficial effects on human skin and health. It causes skin damage, aging, and cancer; however, it is also a primary source of vitamin D. Additionally, UV radiation can impact energy metabolism and has protective effects on several cardiovascular and metabolic disorders in mice and humans. However, the mechanisms of UV protection against these diseases have not been clearly identified.MethodsThis review summarizes the systemic effects of UV radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the nitric oxide (NO), acting as a endogenous vasodilator, can improve blood flow and lower blood pressure, thereby prompting brain health. It has been indicated that exposure to UV radiation in sunlight may lead to the release of NO from the skin into the bloodstream 18 . However, the association of sunlight with brain structure remains incompletely understood now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the nitric oxide (NO), acting as a endogenous vasodilator, can improve blood flow and lower blood pressure, thereby prompting brain health. It has been indicated that exposure to UV radiation in sunlight may lead to the release of NO from the skin into the bloodstream 18 . However, the association of sunlight with brain structure remains incompletely understood now.…”
Section: Introductionmentioning
confidence: 99%
“…has been indicated that exposure to UV radiation in sunlight may lead to the release of NO from the skin into the bloodstream 18 . However, the association of sunlight with brain structure remains incompletely understood now.…”
mentioning
confidence: 99%
“…UV exposure to the skin triggers skin-related biochemical responses and impacts signal transduction pathways in other organs. Furthermore, several studies have suggested that chronic UV exposure can alter the levels of hormones, proteins, and small molecules, such as melanocyte-stimulating hormone 4 , β-endorphin 5 , nitric oxide 6,7 , and urocanic acid 8 , in the skin or blood.…”
Section: Introductionmentioning
confidence: 99%